Enhancing Arabic Reading Skills through the Group Investigation Model Using Padlet - Silvia Rahma Yanti, Silvia; Wildana Wargadinata, Wildana; Shofil Fikri, Shofil (UIN Raden Mas Said Surakarta, 2025)
This research stems from the issue of students’ low engagement and limited comprehension in traditional reading skill instruction. Accordingly, it aims to evaluate the effectiveness of utilizing Padlet media in combination with the Group Investigation model to enhance reading proficiency among students at MTs Islam Wahid Hasyim 1 Malang, employing a quantitative, quasi-experimental approach. The sample consisted of 40 eighth-grade students. The data collection procedures comprised observation, documentation, and testing, while data analysis was carried out through normality and homogeneity tests, followed by hypothesis testing using SPSS version 21. The findings revealed that the integration of Padlet with the Group Investigation model required organizing students into small groups, within which they collaboratively analyzed, interpreted reading texts, discussing meanings and vocabulary, and presenting their findings on Padlet in the form of summaries, notes, or images. The teacher observed and facilitated each group. Afterwards, students presented the results of their investigation and answered questions from other groups. The results of the statistical analysis yielded a significance level of 0.000, which is below the 0.05 significance criterion. Accordingly, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. These findings confirm that the use of Padlet integrated with the Group Investigation model significantly improved students’ reading performance. This research provides useful insights for teachers in designing more interactive and meaningful learning and can serve as a reference for other researchers interested in developing innovative methods in Arabic language education.